2023
DOI: 10.3390/foods12071384
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Serum and Oxygen on the In Vitro Culture of Hanwoo Korean Native Cattle-Derived Skeletal Myogenic Cells Used in Cellular Agriculture

Abstract: Skeletal muscle-derived myogenic cells (SKMCs) are novel protein sources capable of replacing animal meat. However, SKMCs have not been commercialized owing to poor productivity and the high cost of in vitro cell culture. Therefore, we cultured SKMCs in varying serum (5–20%) and oxygen concentrations (5–20%) to investigate the parameters that most impact cell productivity (serum, hypoxia, and culture medium) and examined cell proliferation ability and genes involved in myogenesis/proliferation/apoptosis/reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…However, its expression is influenced by factors such as chicken breed, age, and embryonic age and declines with aging [23][24][25]. Although not of the same species, our previous study revealed that the expression of Pax7 in 2-year-old Korean Bulls was relatively low compared to another group using a 15-day-old Simmental calf [8,26]. Our study focused on isolating fetal myoblasts, typically found at 8-12 days of age [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…However, its expression is influenced by factors such as chicken breed, age, and embryonic age and declines with aging [23][24][25]. Although not of the same species, our previous study revealed that the expression of Pax7 in 2-year-old Korean Bulls was relatively low compared to another group using a 15-day-old Simmental calf [8,26]. Our study focused on isolating fetal myoblasts, typically found at 8-12 days of age [27,28].…”
Section: Discussionmentioning
confidence: 99%